Incorporating Islah Principles into Restorative Justice: Bridging Contemporary Legal Practice and Islamic Values - Joko Budi Darmawan; Fendy Suhariadi; Suparto Widjojo; Mia Amiati; Amjad Hamad Abdullah (Faculty of Sharia, IAIN Metro, 2025)
The concept of islah in Islamic law emphasizes peaceful conflict resolution through mediation, compromise, and forgiveness—principles that align closely with the restorative justice approach in modern legal systems. This article aims to explore the integration of islah values into the restorative justice framework, as well as how the concept of reconciliation in both positive law and Islamic law can be recontextualized in the contemporary era. This study employs a qualitative method using a normative-juridical and comparative approach based on a literature review of primary and secondary sources, including classical Islamic legal texts (turath), statutory regulations, and policy documents on restorative justice practices in Indonesia and selected Muslim-majority countries. The findings indicate that islah values hold significant potential to enrich restorative justice practices, particularly in strengthening participatory justice and the restoration of social relationships. The recontextualization of reconciliation not only opens space for dialogue between positive law and Islamic law but also offers a more humanistic, contextual, and community-responsive model of conflict resolution. The article recommends enhancing legal regulations to incorporate islah-based approaches within Indonesia's criminal justice system as part of a broader effort to harmonize national legal norms with Islamic values. Its academic contribution lies in providing a constructive foundation for the theoretical and normative integration of islah values into the national legal system through restorative justice while offering a new paradigm for resolving criminal cases in a more contextualized manner.